2005
DOI: 10.1159/000081781
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pregnancy on Intraobserver and Intertechnique Agreement in Intraocular Pressure Measurements

Abstract: Aim: To evaluate the effect of pregnancy on intraobserver and intertechnique agreement for intraocular pressure (IOP) measurements. Material and Methods: Right eyes of 88 healthy women who were likely to become pregnant and of 94 healthy age-matched females were included in the study. Complete ocular examinations were performed on each eye. IOP measurements were obtained by Goldmann, Schiötz and non-contact tonometers (NCT) during 3-week exam periods before (within 6 weeks of conception) and during pregnancy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 40 publications
1
27
1
1
Order By: Relevance
“…Glaucoma: Glaucoma is another preexisting disease modified by pregnancy. As mentioned earlier, intraocular pressure is decreased during pregnancy [11][12][13][14][15]. Intraocular pressure decreases during the second trimester and continues to decrease with the advancing pregnancy [13].…”
Section: Effect Of Pregnancy On Preexisting Ocular Disordersmentioning
confidence: 62%
See 2 more Smart Citations
“…Glaucoma: Glaucoma is another preexisting disease modified by pregnancy. As mentioned earlier, intraocular pressure is decreased during pregnancy [11][12][13][14][15]. Intraocular pressure decreases during the second trimester and continues to decrease with the advancing pregnancy [13].…”
Section: Effect Of Pregnancy On Preexisting Ocular Disordersmentioning
confidence: 62%
“…As mentioned earlier, intraocular pressure is decreased during pregnancy [11][12][13][14][15]. Intraocular pressure decreases during the second trimester and continues to decrease with the advancing pregnancy [13]. In most cases, lower intraocular pressure means glaucoma improves with pregnancy [49][50].…”
Section: Effect Of Pregnancy On Preexisting Ocular Disordersmentioning
confidence: 81%
See 1 more Smart Citation
“…Outros fatores que causam a aceleração de retinopatia diabética neste grupo inclui duração do diabetes (19) , hipertensão associada à gravidez e pré-eclâmpsia (20) , normalização rápida dos níveis de glicose durante a gravidez (21) , controle glicêmico não rigoroso pré-gravídico (19) e mudança no fluxo sanguíneo retiniano (22) . Diabetes gestacional, na ausência de diabetes pré-existente, não mostra uma associação similar com retinopatia diabética.…”
Section: A -Retinopatia Diabéticaunclassified
“…Accuracy and reliability are two equally important factors that determine the usefulIn their article, Akar et al [1] concluded that perfect intraobserver agreement in intraocular pressure (IOP) readings of pregnant subjects was obtained with non-contact tonometer (NCT). They suggested that NCT is a viable option for IOP measurements during the follow-up of pregnant patients at risk of glaucoma.…”
mentioning
confidence: 99%